Project-based learning for health: a university pedagogical experience: Aprendizaje basado en proyectos para la salud: una experiencia pedagógica universitaria - Carcausto, Wilfredo (2020)
Objective: To know the pedagogical experience of the application of project-based learning (ABP) in students of the third cycle of nursing at a university in North of Lima. Materials and methods: The design used was quantitative and descriptive. A total of 21 work groups participated, consisting of three to four students. For data collection, a rubric and an interview guide were used. Results: Of the 21 groups of students, 52.4% (n=11) had a good level of learning with the ABP methodology, however 4.8% (n=1) had a regular level. Two categories emerged from the interviews: benefits and difficulties that could have been encountered in the development of the pedagogical experience. Conclusions: In most of the groups the level of global learning with the ABP methodology was good. With the use of ABP, a pleasant environment was promoted to adequately develop the skills of understanding the problem, managing activities, and social communication. Keywords: Problem-Based Learning; Students, Health Occupations; Peru (Source: MeSH, NLM).